IFAE 2007 Incontri di Fisica delle Alte Energie Italian Meeting on High Energy Physics - Carlino, G.; D'Ambrosio, G.; Merola, L.; Paolucci, P.; Ricciardi, G.; SpringerLink (Online service) (Milano : Springer Milan : Imprint: Springer, 2008)
This book collects the Proceedings of the Workshop "Incontri di Fisica delle Alte Energie (IFAE) 2007, Napoli, 11-13 April 2007". This is the sixth edition of a series of meetings on fundamental research in particle physics and was attended by about 160 researchers. Presentations, both theoretical and experimental, addressed the status of Physics of the Standard Model and beyond, Flavour phyisc, Neutrino and Astroparticle physics, new technology in high energy physics. Special emphasis was given to the expectations of the forthcoming Large Hadron Collider, due in operation at the end of 2007. The venue of plenary sessions interleaved with parallel ones allowed for a rich exchange of ideas, presented in these Proceedings, that form a coherent picture of the findings and of the open questions in this extremely challenging cultural field. The venue of plenary sessions interleaved with parallel ones allowed for a rich exchange of ideas, presented in these Proceedings, that form a coherent picture of the findings and of the open questions in this extremely challenging cultural field.
Plenary Session -- D 0 - Mixing -- The Presence of Giuseppe Occhialini in the Centenary of his Birth -- Standard Model -- Electroweak Physics with CMS and ATLAS -- Minimum Bias and Underlying Event at LHC -- Top Physics at the Tevatron Collider -- Top Physics at the LHC -- Standard Model Higgs Searches at CDF and DØ -- Search for the Standard Model Higgs at LHC -- Rescuing H ? in VBF at the LHC by Requiring a Central Photon -- Vector Boson Pair Production via Vector Boson Fusion at NLO QCD -- A New Method for the Numerical Evaluation of One-Loop Amplitudes -- QCD Corrections to J/? and ? Production at Hadron Colliders -- Newly Observed Charmed States: the Case of X(3872) -- Physics Beyond the Standard Model -- Supersymmetry Searches at the Tevatron -- New Gauge Bosons and Extra Dimensions at the LHC -- Stop-Chargino Production at LHC -- New Physics in the Top Sector at LHC -- Early Supersymmetry Searches with ATLAS Detector at LHC -- Neutralino Spin Measurement with ATLAS Detector at LHC -- Heavy Flavour Physics -- ?m s , ?? s and ? s Measurements at Tevatron -- Model-independent Analysis of ?F = 2 Transitions -- SUSY Effects (or Lack Thereof) in ?F = 2 Transitions -- Charged Kaons and V us at KLOE -- |V ub | from Inclusive B Decays and the Analytic Coupling Model -- Resummation and Mass Effects in b Decays -- Unitarity Angles and Sides Measurement at B a B ar -- The ? X s ? Decay at NNLO -- Charmless b-Hadron Decays at CDF -- Rare Beauty Decays with ATLAS and CMS Experiments at LHC -- B ? K*?+?? as a Probe of Universal Extra Dimensions -- Lepton Flavour Violation in SUSY SO(10) -- ? Physics at B a B ar -- New Physics and the MEG Experiment -- Neutrinos and Astroparticle Physics -- Status of Neutrino Oscillations -- Analysis of Neutrino Signals from SN1987A -- Accelerator Neutrino Physics: Status and Perspectives in Europe -- Neutrino Oscillation Measurement at Reactors -- Gamma-Ray Astronomy -- Measurement of Neutrino Absolute Mass -- The Lyman-? Forest as a Probe of the Coldness of Dark Matter -- Km3 Cherenkov Telescopes for High Energy Neutrino Astronomy -- Cosmological Constraints on Neutrino Masses -- High Intensity Neutrino Beams and Standard Model Precision Measurements -- The Detection of Gravitational Waves -- MiniBooNE First Results on a Search for ? e Appearance at the ?m 2 ? 1 eV2 Scale -- New Technologies -- The International Linear Collider -- DAFNE2: Prospects for e + e ? Physics at Frascati -- Level-1 Trigger Systems for LHC Experiments -- CDF Computing Experience: an Overview -- Italian Grid Infrastructures -- Overview of Analysis Models for High Energy Physics Experiments.
Keywords: Nuclear physics; Quantum field theory; String theory; Heavy ions; Elementary particles (Physics).; Astrophysics; Particle acceleration; Particle and Nuclear Physics; Quantum Field Theories, String Theory; Nuclear Physics, Heavy Ions, Hadrons; Elementary Particles, Quantum Field Theory; Astrophysics and Astroparticles; Particle Acceleration and Detection, Beam Physics